2014
DOI: 10.1093/ilar/ilu042
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analyses of Animal Studies: An Introduction of a Valuable Instrument to Further Improve Healthcare

Abstract: In research aimed at improving human health care, animal studies still play a crucial role, despite political and scientific efforts to reduce preclinical experimentation in laboratory animals. In animal studies, the results and their interpretation are not always straightforward, as no single study is executed perfectly in all steps. There are several possible sources of bias, and many animal studies are replicates of studies conducted previously. Use of meta-analysis to combine the results of studies may lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 31 publications
1
136
1
Order By: Relevance
“…To account for anticipated heterogeneity, we pooled effect sizes using random-effects meta-analysis, which considers the within-study and between-study variability and weights each study accordingly. Heterogeneity was quantified using I2 and T2 statistics 29 , 31 . Studies with missing data on any of the pre-defined experimental variables were excluded from the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To account for anticipated heterogeneity, we pooled effect sizes using random-effects meta-analysis, which considers the within-study and between-study variability and weights each study accordingly. Heterogeneity was quantified using I2 and T2 statistics 29 , 31 . Studies with missing data on any of the pre-defined experimental variables were excluded from the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…25 It has been evident that UC is more common in Asia and the United States than CD, but recent epidemiological studies have shown that the incidence of CD is rising up. 45 Thus, this study was intended to provide a systematic review and a metaanalysis of published original research articles that have assessed the effects of ALA and its derivative 'AL-1' on the IBD symptoms. 28 A number of argumentative F I G U R E 1 Chemical structures of A, alpha lipoic acid; B, andrographolide acid; and C, andrographolide-lipoic acid-1 factors, such as dysregulation of immune cascades and imbalanced cytokine networks, environment, genetics, and manipulation of normal flora are mostly suspected as IBD etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, lessons can be learned from the experiences made when adapting and applying meta-analyses to pre-clinical animal studies (Vesterinen et al 2014, Hooijmans et al 2014b). Meta-analysis of human epidemiological studies has been applied to assess neurobehavioral effects of metal or organic solvent exposure in an occupational setting (e.g., Goodman et al 2002; Meyer-Baron 2005).…”
Section: Preamblementioning
confidence: 99%